MicroRNA miR-155 is a biomarker of early pancreatic neoplasia - Habbe, Nils (2009)
BACKGROUND: Intraductal papillary mucinous neoplasms (IPMNs) are non-invasive precursor lesions of pancreatic cancer. Misexpression of microRNAs (miRNAs) is commonly observed in pancreatic adenocarcinoma. In contrast, miRNA abnormalities in pancreatic cancer precursor lesions have not been documented. EXPERIMENTAL DESIGN: Relative expression levels of a panel of twelve miRNAs upregulated in pancreatic cancers were assessed in 15 non-invasive IPMNs, using quantitative reverse transcription PCR (qRT-PCR). Two significantly overexpressed miRNAs—miR-155 and miR-21—were evaluated by locked nucleic acid in situ hybridization (LNA-ISH) in a panel of 64 archival IPMNs. The expression of miR-155 and miR-21 was also evaluated in pancreatic juice samples obtained from ten patients with surgically resected IPMNs and five patients with non-neoplastic pancreato-biliary disorders (“disease controls”). RESULTS: Significant overexpression by qRT-PCR of ten of the twelve miRNAs was observed in the 15 IPMNs versus matched controls (p < 0.05), with miR-155 (mean 11.6-fold) and miR-21 (mean 12.1-fold) demonstrating highest relative fold-changes in the precursor lesions. LNA-ISH confirmed the expression of miR-155 in 53 of 64 (83%) IPMNs compared to 4 of 54 (7%) normal ducts, and of miR-21 in 52 of 64 (81%) IPMNs compared to 1 of 54 (2%) normal ducts, respectively (p < 0.0001). Upregulation of miR-155 transcripts by qRT-PCR was observed in 6 of 10 (60%) IPMN-associated pancreatic juice samples compared to 0 of 5 (0%) disease controls. CONCLUSIONS: Aberrant miRNA expression is an early event in the multistage progression of pancreatic cancer, and miR-155 warrants further evaluation as a biomarker for IPMNs in clinical samples.